PASTA FEED ENRICHMENT FERMENTED WITH MESENTERIC PARTS OF PANGASIUS ON THE GROWTH AND SURVIVAL OF ASIAN REDTAIL CATFISH (Hemibagrus nemurus) LARVAE - Manik, Yesi Sartika Br; Aryani, Netti; Heltonika, Benny (Asian Journal of Aquatic Sciences, 2024)
Pasta feed is an alternative replacement feed naturally occurring in cultivating Asian redtail catfish (Hemibagrus nemurus) larvae. However, pasta feed is not yet able to completely replace the Tubifex sp, and enrichment feed pasta with oils from mesenteric waste catfish is expected to improve the performance of pasta feed. This research aimed to determine the effect of enriching fermented pasta feed with waste oil from the mesenteric parts of catfish on the growth and survival of Asian redtail catfish larvae. This research used an experimental method with the design used, a Completely Randomized Design (CRD), one factor, and five treatments with three replications. This research was carried out from March to April 2024 at the Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty, Universitas Riau. The research results show the influence of enrichment of fermented pasta feed with pangasius mesenteric fish oil on the growth and survival of Asian redtail catfish larvae. Given larvae feed fermented paste + fish oil from pangasius mesenteric waste 12 % produce growth and survival highest with an absolute weight of 1.63 g, absolute length of 5.33 cm, specific growth rate of 14.73%/day, survival of 84.44%, type A cannibalism index of 13.77%, and normal mortality of 1.77%. Water quality parameters such as water temperature range from 27-28.9 °C, pH ranges from 5-7, and DO ranges from 5.1-8.1 mg/L.